2005
DOI: 10.1002/pros.20127
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal ultrasound versus magnetic resonance imaging for detection of rectal wall invasion by prostate cancer

Abstract: TRUS is a highly sensitive diagnostic modality for rectal wall involvement in patients with locally advanced prostate cancer. Although MRI is very specific, it cannot reliably rule out rectal involvement in the presence of a positive TRUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The possible explanation is local control, removing the potential source of future metastases, and improving the response to systemic therapy [44]. Although it is inappropriate to make inferences regarding the role of TPE in the management of prostate cancer with rectal involvement based on the findings in this retrospective review, we and others [49] believe that TPE should be further evaluated as treatment strategies for selected patients, especially in nonextrarectal metastatic hormonally untreated patients, because they may provide better local control and a potential long-term survival and cure.…”
Section: Discussionmentioning
confidence: 96%
“…The possible explanation is local control, removing the potential source of future metastases, and improving the response to systemic therapy [44]. Although it is inappropriate to make inferences regarding the role of TPE in the management of prostate cancer with rectal involvement based on the findings in this retrospective review, we and others [49] believe that TPE should be further evaluated as treatment strategies for selected patients, especially in nonextrarectal metastatic hormonally untreated patients, because they may provide better local control and a potential long-term survival and cure.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, two more studies on larger cohorts of patients comparing TRUS versus MRI in staging of prostate and rectal cancer were published (25,26) . Both studies found higher accuracy achieved using TRUS than MRI.…”
Section: Discussionmentioning
confidence: 99%
“…3D‐TRUS was a simple and easy investigation, which did not require special preparation. It is cheap, by contrast with other imaging methods of current interest, especially endorectal MRI [15]. 3D‐TRUS is easy to interpret by experts in conventional TRUS.…”
Section: Discussionmentioning
confidence: 99%